Hydrogen energy storage integrated hybrid renewable energy systems: A review analysis for future research directions - Arsad A.Z.; Hannan M.A.; Al-Shetwi A.Q.; Mansur M.; Muttaqi K.M.; Dong Z.Y.; Blaabjerg F. (Elsevier Ltd, 2023)
Electric power transmission networks; Energy conservation; Hydrogen storage; Search engines; Sustainable development; Bibliometrics analysis; Control methods; Future research directions; Highly cited article; Hybrid renewable energies; Hydrogen energy storage system; Hydrogen energy storages; Microgrid; Renewable energies; Storage systems; Renewable energy resources